2020
DOI: 10.3389/fphar.2020.522213
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of the Essential Oil of Thymbra capitata (L.) Cav., Origanum dictamnus L. and Salvia fruticosa Mill. And a Case of Plant-Based Pharmaceutical Development

Abstract: This review performs a comprehensive assessment of the therapeutic potential of three native herbs of Crete (Thymbra capitata (L.) Cav., Salvia fruticosa Mill. and Origanum dictamnus L.), their phytochemical constituents, health benefits and issues relevant to their safety, within a translational context. Issues discussed comprise: 1) Ethnopharmacological uses of the three herbs, reviewed through an extensive search of the literature; 2) Systematic analysis of the major phytochemical constituents of each plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 122 publications
2
24
0
Order By: Relevance
“…It presents remarkable anti-viral properties against Influenza A and B strains and HRV14 (Tseliou et al, 2019), while it is safe in both experimental animals (Kalyvianaki et al, 2020) and humans (Duijker et al, 2015). Its properties have been recently reviewed in reference (Pirintsos et al, 2020). Here, we extend these previous findings, by providing in vitro evidence about its antiviral activity against SARS-CoV-2 infected VERO cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…It presents remarkable anti-viral properties against Influenza A and B strains and HRV14 (Tseliou et al, 2019), while it is safe in both experimental animals (Kalyvianaki et al, 2020) and humans (Duijker et al, 2015). Its properties have been recently reviewed in reference (Pirintsos et al, 2020). Here, we extend these previous findings, by providing in vitro evidence about its antiviral activity against SARS-CoV-2 infected VERO cells.…”
Section: Discussionsupporting
confidence: 55%
“…The main compounds are carvacrol (53%), eucalyptol (13%), β-Caryophyllene (3%), p-Cymene (1.32%), γ-Terpinene (1.17%), Borneol (1.68%) and α-Terpineol (1.06%). As reviewed recently (Pirintsos et al, 2020), none of these compounds have been reported as anti-virals. However, work in progress in our group has identified specific viral targets for some of these constituents, with a direct impact on viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no natural product has been proposed to target the N protein. Recently, we have reported that a combination of three aromatic plants ( Thymbra capitata (L.) Cav., Origanum dictamnus L., Salvia fruticosa Mill., 21 and references therein) is efficient against upper respiratory tract viral infections. Further in vitro studies revealed that a primary target of this preparation is the viral nucleoprotein (NP), inhibiting its nuclear translocation, 22 and impairing viral protein transcription, while a proof‐of‐concept clinical trial suggests a possible action of the preparation in mild, ambulatory, COVID‐19 positive patients (Lionis et al 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter application includes their use in a wide range of ailments, including digestive, respiratory, renal, hepatic, neurological, cardiac, blood circulation and metabolic, among others [16][17][18][19]. In fact, many authors confirmed the potential bioactive properties of Salvia constituents, such as those in essential oils [20][21][22][23]. More recently, polar extracts rich in phenolic compounds have also emerged as promising bioactive agents, enabling them to be applied in different areas [15,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%